The Future of Gaming: How Artificial Intelligence is Revolutionizing the Industry - Dariana Gomez-Alvarez; Michel Lopez-Franco; David Bonilla Carranza; Carlos Lopez-Franco; Lilibet Lopez-Franco (ReCIBE)
Artificial Intelligence (AI) is not just a tool for improving video games; it is revolutionizing the entire industry. This opinion paper explores how AI is transforming gaming experiences, enhancing player engagement, and reshaping game design. We argue that AI’s role in gaming is not just beneficial but essential for the future of interactive entertainment. Through an examination of current trends and future possibilities, we provide our perspective on the profound impacts of AI on the gaming world.